Prevalence and Risk Factors Associated with Neck Pain in College Students (JURNAL PROTEKSI KESEHATAN, 2023)
Neck pain can be caused by ergonomic factors such as doing activities that cause the neck to be in a static position and experiencing repetitive motion for a long time. This study aims to determine the prevalence and risk factors for neck pain in college students. An analytic observational study with a cross-sectional approach was used to 231 UIN Jakarta Public Health students aged ≥18 years. Data was collected through an online questionnaire and analyzed by the chi-square test. The results showed the prevalence of neck pain in college students was 25% with the duration of using a laptop/computer as a risk factor that was significantly associated with the incidence of neck pain (pv = 0.02). The prevalence of neck pain in college students is still quite high. There is a need for education related to risk factors for neck pain among students, especially those who conduct online lectures.